Variantes genéticas asociadas con niveles de hemoglobina fetal muestran diversos orígenes étnicos en pacientes colombianos con anemia falciforme (2015)
etal hemoglobin is an important factor in modulating the severity of sickle cell anemia. Its level in peripheral blood underlies strong genetic determination. Associated loci with increased levels of fetal hemoglobin display population-specific allele